Karakteristik Komite Audit dan Audit Report Lag (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2020) - Djuminah, Djuminah; Wijayanto, Agung (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2022)
This research aims at examining the influence of Audit Committee upon Audit Report Lag. The observation was taken based on 198 sample data in the years of 2019 - 2020. Its source was from listed manufacturing industry in BEI. The results of this study shows that Audit Committee’s Meeting, The Audit Committee’s Financial Skill and Size of Audit Commitee do not affect to Audit Report Lag. There is a control variable: a close geographical position of both auditor and client, gives a positive impact to The Audit Report Lag. Keywords: audit Committee’s meeting, audit committee’s financial skill, size of audit commitee and audit report lag. Penelitian ini bertujuan untuk menguji pengaruh Komite Audit terhadap Audit Report Lag. Pengamatan diambil berdasarkan 198 sampel data pada tahun 2019 - 2020. Sumbernya dari industri manufaktur yang terdaftar di BEI. Hasil penelitian ini menunjukkan bahwa Rapat Komite Audit, Keterampilan Keuangan Komite Audit dan Ukuran Komite Audit tidak berpengaruh terhadap Audit Report Lag. Ada variabel kontrol: posisi geografis yang dekat antara auditor dan klien, memberikan dampak positif terhadap The Audit Report Lag.